Forms of unknowing in Victorian poetry - McGhee, F (2021)
This thesis argues that Victorian poets were persistently drawn to the experience of partial, uncertain, or elusive knowledge, situations in which knowing is felt to be simultaneously tantalising and potentially entrapping or chimerical: a set of conditions I group under the term ‘unknowing’. Exploring the ways in which the idea of knowledge in the nineteenth century was saturated in value and feeling, I show how the resistance of certain objects to being fully known (people, God, art, nature, the future) could generate not merely frustration and disappointment but fresh sources of possibility and pleasure. For the poets I study, such concerns were intimately linked to the question of poetry’s own relationship to knowledge. In the fibres of their poetry, as well as in the writings of some of the period’s most inventive thinkers, I trace a vital and availing tradition which stresses how poetry may sharpen our awareness of that which exceeds or escapes our knowing. My first chapter reads the poetry of Arthur Hugh Clough as a sustained dialogue with Ralph Waldo Emerson’s critique of ‘knowingness’. My second connects Robert Browning’s interest in the natural world with notions of foiled or occluded knowledge, drawing on the writings of John Ruskin. My third chapter proposes two ways of thinking about knowing in the poetry of Dante Gabriel Rossetti: an aesthetics of vagueness stemming from Renaissance art theory, and the dreamlike phenomenology of déjà vu. My fourth chapter pursues Alice Meynell’s interest in God’s hiddenness as a potential resource of faith, linking it to the thought of John Henry Newman and the figure of the Virgin Mary. My final chapter explores Thomas Hardy’s attention to the difficulties of knowing (and being known by) other people, showing how more fruitful modes of engagement may depend upon relinquishing the desire for secure knowledge.